POST HARVEST PRESERVATION OF FRUITS AND VEGETABLES; STUDY ON CARROTS PRESERVED BY MODIFIED ATMOSPHERE PACKAGING (MAP) TECHNOLOGY (Biological Sciences - PJSIR, 2002)
The objective of this study is to note the results of modified Atmosphere Packaging (MAP) Technology for post harvest preservation of carrots (Daucus carrota L.). It was observed that peeling treatment, film type and days of storage had a significant effect on  CO, and  0  percentages within  bags of carrots stored  at  7°C.  The  bags with  peeled  carrots contained significantly less CO , 9.4% and more 0 , 16. 1% than non-peeled carrots, 17.6% CO and 14.3% 0 durin g the 28 day 2                                               2                                                                                                          2                                  2storage period